Membangun Perdamaian Antar Umat Beragama Melalui Pengajaran Pendidikan Agama Kristen di Indonesia - Istinatun, Hestyn Natal; Sirait , Junio Richson (Basilius Eirene Press, 2022)
Peace between religious communities is the ultimate goal of every tolerant attitude that leaders in Indonesia continuously pursue. However, the government only uses Pancasila and Citizenship Education subjects to form a society that has an attitude of respect for other beliefs. In fact, religious subjects can also be an essential lesson in building an attitude of respect. This study aims to find the teaching of Christian Religious Education that can contribute greatly to the advancement of inter-religious peace in Indonesia. Therefore, the researcher uses a qualitative descriptive research approach with a literature review technique to find the teaching of Christian Religious Education which has a major contribution to building reconciliation. The results found in this study are that Christian Religious Education teaching can increase awareness, and tolerance among religious people and fortify them from radical understanding.